Delusions in Context - Bortolotti, Lisa (Springer Nature, 2018)
This open access book offers an exploration of delusions-unusual beliefs that can significantly disrupt people's lives. Experts from a range of disciplinary backgrounds, including lived experience, clinical psychiatry, philosophy, clinical psychology, and cognitive neuroscience, discuss how delusions emerge, why it is so difficult to give them up, what their effects are, how they are managed, and what we can do to reduce the stigma associated with them. Taken as a whole, the book proposes that there is continuity between delusions and everyday beliefs. It is essential reading for researchers working on delusions and mental health more generally, and will also appeal to anybody who wants to gain a better understanding of what happens when the way we experience and interpret the world is different from that of the people around us.